Sistem Akses Kontrol Laboratorium Menggunakan Kartu Tanda Mahasiswa - Alexander Prasetya Widodo; Resmana Lim; Lily Puspa Dewi (Jurnal Infra, 2020)
Attendance procces is a record of presence of student and teacher in a college courses. With this record of presence, the student can figure out how many courses he attented to. Combining technology and presence that currently use in laboratory, the goal is to elevate effectiveness in attendance procces in the laboratory and access to the laboratory and also to make student easier at attendance proccess and also minimalize the mistake that would be happen.Manually record the presence gradually left behind if the process isnt getting update soon. There by, the process need new technology that can make controlling and recording of laboratory use and can also be use to record the attendance for student that has course in that laboratory easier with usage of the device that called Radio Frequency Identification and Detection tag.This access control system of laboratory use Raspberry pi and have website. Access control system of laboratory connect directly with raspberry pi, magnetic door lock, and also rfid tag, making direct access control granted to people that had a right to use that laboratory with student idenfitication card.